The Effect of Financial and Non-Financial Compensation towards Employee Job Satisfaction - Thapa, Roshan (Kathford Journal of Engineering and Management, 2023)
The main purpose of the study was to examine the effect of financial and nonfinancial compensation towards employee job satisfaction with their education, working department. To produce numeric analysis and testing hypothesis, the researchers used ANOVA Test to measure education level, job position and, working departments with employees’ job satisfaction. The Ordinary Least Square (OLS) Method was used to measure the effect of financial and non-financial compensation towards employees’ job satisfaction. The analysis was performed through SPSS 26. The testing included 150 respondents of assistant, officer and, managerial level from administration, operation and, credit departments of commercial banks from Maharajgung to Balaju Ringroad Kathmandu. The main research findings revealed that financial and nonfinancial compensation had a significant effect on employee job satisfaction. The finding also shows that the job satisfaction is significantly depends on their current education, job position and, working department too. Similarly, the impact of financial compensation towards job satisfaction was higher than that of non-financial compensation in employees’ job satisfaction. The financial and non-financial compensation had positive impact on employees’ job satisfaction.